2000
DOI: 10.1093/jn/130.4.802
|View full text |Cite
|
Sign up to set email alerts
|

Four-Day Multimedia Diet Records Underestimate Energy Needs in Middle-Aged and Elderly Women as Determined by Doubly-Labeled Water

Abstract: Systematic problems exist in the quantification of food intake in populations using traditional self-reported measures. The objective of this study was to determine the effectiveness of an innovative multimedia diet record (MMDR) for dietary energy intake assessment. Dietary intake was estimated by combining the use of a microcassette tape recorder and 35-mm camera in 53 women whose ages ranged from 50 to 93 y (64.9 +/- 11.3 y), with body weights of 62.4 +/- 12.2 kg and body mass indexes (BMI) of 24.4 +/- 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 17 publications
0
58
0
3
Order By: Relevance
“…However, the participants in this adult study were all college-aged nutrition students who, due to their age and education level, would be expected to follow the study instructions more closely than a broad population of school-aged children and who, due to their specific nutrition training, would also be more capable of keeping an accurate food diary than our study population. The second adult study that employed photographic food records in adults observed a greater extent of underreporting than was observed in the current pediatric cohort (Kaczkowski et al, 2000).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…However, the participants in this adult study were all college-aged nutrition students who, due to their age and education level, would be expected to follow the study instructions more closely than a broad population of school-aged children and who, due to their specific nutrition training, would also be more capable of keeping an accurate food diary than our study population. The second adult study that employed photographic food records in adults observed a greater extent of underreporting than was observed in the current pediatric cohort (Kaczkowski et al, 2000).…”
Section: Discussionmentioning
confidence: 49%
“…However, those subjects that forgot to carry their cameras at all times also forgot to carry their diet diaries so both methods suffer from this drawback. The advantage of the diet diary is that foods can be recorded in retrospect which, although not ideal due to increases in misreporting under these circumstances (Dwyer et al, 1987;Kaczkowski et al, 2000;Black and Cole, 2001;Goris et al, 2001), is not possible with the photographic method. Therefore, it would be advantageous to issue instruction on portion sizes and standard recording methods when beginning a photographic food record so that foods could be recorded on paper or later in the day if subjects forget to take photographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Professional researchers can also benefit in performing diet intake studies with the help of lifelog browsing and annotation tools. Both audio recorders and cameras are combined in [25]. According to [26], individuals self-reported energy intake frequently and substantially underestimates true energy intake, while Microsoft SenseCam wearable camera can help more accurately report dietary intake within various sporting populations.…”
Section: Typical Applications In Assistive Livingmentioning
confidence: 99%